DETEKSI FORMALIN PADA IKAN ASIN MENGGUNAKAN UBI JALAR UNGU (Ipomea batatas L.) - Andrew Setyawan; Evi Hanizar (saintifika, 2021)
The content of formalin in salted fish needs to be known by the public in an easy and inexpensive way. Purple sweet potato (Ipomoea batatas) is one of the plants that contains anthocyanin which will show a color change when reacted with formalin. This study aims to determine whether purple sweet potato extract can detect formalin content in salted fish. The method used is a pure experiment with 5 treatments and 5 replications. Salted fish samples were made by the researcher himself, while purple sweet potato was extracted with a dose ratio of 1:1, 1:2 and 1:3 (v purple sweet potato extract /v aquadest). The observation parameter was the time when the color changed from purple to reddish in the salted fish sample after being dripped with purple sweet potato extract. The data were analyzed statistically using the Kurskall-Wallis test and continued with Duncan's test. The results of the analysis showed that purple sweet potato extract could detect the presence of formalin in salted fish samples (p < 0.05). The treatment with a dose of 1: 1 was able to detect the fastest formalin content at 735.40 seconds compared to treatment 1: 2 (915.20) and treatment 1: 3 (1038.40). This time is close to the time required by the positive control treatment (607.80). The conclusion of this study confirms that purple sweet potato can be used by the public to detect formalin content in food.